2023
DOI: 10.1002/app.54963
|View full text |Cite
|
Sign up to set email alerts
|

Selective thermal recycling for graphene growth on natural substrates: A comparative study on life cycle assessment, energy consumption, and mechanical performance in recompounding

Havva Baskan‐Bayrak,
Atakan Kocanali,
Burcu Saner Okan

Abstract: Manufacturing of carbon‐based materials from waste thermoplastics is a keystone to reduce adverse environmental impacts. There are numerous attempts for sustainable graphene manufacturing from various waste sources by thermal treatment but there is no clear distinction on the effective conversion process by addressing reliable CO2 footprints. This study provides a comprehensive benchmarking study on the conversion of waste polypropylene plastics coming from yogurt containers into graphene on the substrate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…Despite these advancements, achieving precise control over graphene properties, including layer number, morphology, crystallinity, and size, while overcoming challenges in CO 2 conversion, remains critical for sustainable graphene production. Nevertheless, recent researches demonstrates promising strides in optimizing methods and controlling graphene growth, offering potential solutions for advancing this field towards sustainable and efficient graphene manufacturing [36,56,165]. For instance, Bayrak-Baskan et al optimized pyrolysis method at a suitable temperature and demonstrated elevated temperatures resulting in higher graphene yields by facilitating the breaking of C-H and C-C bonds of waste plastic as carbon source [165].…”
Section: Integration Of Co 2 Into Graphene During Indirect Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advancements, achieving precise control over graphene properties, including layer number, morphology, crystallinity, and size, while overcoming challenges in CO 2 conversion, remains critical for sustainable graphene production. Nevertheless, recent researches demonstrates promising strides in optimizing methods and controlling graphene growth, offering potential solutions for advancing this field towards sustainable and efficient graphene manufacturing [36,56,165]. For instance, Bayrak-Baskan et al optimized pyrolysis method at a suitable temperature and demonstrated elevated temperatures resulting in higher graphene yields by facilitating the breaking of C-H and C-C bonds of waste plastic as carbon source [165].…”
Section: Integration Of Co 2 Into Graphene During Indirect Processesmentioning
confidence: 99%
“…Nevertheless, recent researches demonstrates promising strides in optimizing methods and controlling graphene growth, offering potential solutions for advancing this field towards sustainable and efficient graphene manufacturing [36,56,165]. For instance, Bayrak-Baskan et al optimized pyrolysis method at a suitable temperature and demonstrated elevated temperatures resulting in higher graphene yields by facilitating the breaking of C-H and C-C bonds of waste plastic as carbon source [165]. Furthermore, adjusting substrate type, size, and surface composition enables precise control over graphene growth dimensions, offering an opportunity to utilize waste materials as potential carbon sources.…”
Section: Integration Of Co 2 Into Graphene During Indirect Processesmentioning
confidence: 99%